Adrenal Insufficiency - Aetiology, Diagnosis and Treatment (Delta Medical College Journal, 2015)
Adrenal insufficiency is caused by either primary adrenal failure or by hypothalamic-pituitary impairment of the corticotropic axis. Adrenal insufficiency, first codified in 1855 by Thomas Addison, remains relevant in 2014 because of its lethal nature. Though, it is a rare disease but is life threatening when overlooked. Main presenting symptoms such as fatigue, anorexia and weight loss are nonspecific, thus diagnosis is often delayed. The diagnostic work-up is well established but some pitfalls remain. The diagnosis is adequately established by the 250 ?g ACTH (adrenocorticotropic hormone) stimulation test in most cases. Glucocorticoids provide life saving treatment but long-term quality of life is impaired, perhaps because therapy is not given in a physiologic way. Dehydroepiandrosterone-replacement therapy has been introduced that could help to restore quality of life. It may be useful in pubertal girls, but not in adults. Monitoring of glucocorticoid-replacement is difficult due to lack of objective methods of assessment and is therefore largely based on clinical grounds. Thus, long-term management of patients with adrenal insufficiency remains a challenge, requiring an experienced specialist. DOI: http://dx.doi.org/10.3329/dmcj.v3i1.22238 Delta Med Col J. Jan 2015; 3(1): 36-47